Bilateral Progressive Visual Loss in an Epileptic, Mentally Retarded Boy - Guerriero, Silvana (Medknow Publications, 2011)
Leber’s hereditary optic neuropathy (LHON) is a maternally inherited, monosymptomatic disorder, characterized by severe central vision loss and optic atrophy that most frequently affects young men. The classic LHON phenotype is associated to three mitochondrial DNA mutations, mostly homoplasmic, in the Mt-ND4, Mt-ND6, and Mt-ND1 genes, encoding for complex I subunits of the mitochondrial respiratory chain. Rare cases have been described in the literature in association with variable central nervous system involvement in a syndromic form called LHON ‘plus.’ In the present study, we report the case of a 16-year-old boy with the 3460/ND1 mutation who presented with epilepsy, migraine, and mental retardation as non-ophthalmic features. We also investigated his relatives who all had the 3460/ND1 mutation.